The impact of lean manufacturing practices on operations performance: A study on Indonesian manufacturing companies - Nawanir, Gusman; Othman, Siti Norezam; Lim, Kong Teong (2010)
The relationships between lean practices and operations performance were investigated in this study. Lean practices include flexible resources, cellular layouts, pull system, small lot production, quick setup, uniform production level, quality at the source, total productive maintenance, and supplier networks. Operations performance measures include quality, flexibility, lead time reduction, and cost reduction. Based on the theoretical framework, four hypotheses were developed and tested statistically. The study was cross-sectional study using survey methodology. The survey was carried out randomly in large Indonesian manufacturing companies based on the data provided by the Data and Information Center of Indonesian Ministry of Industry with the final number of respondents was 139. The study hypotheses were tested statistically by applying Pearson correlation analysis, multiple regression analysis, principal component analysis, and simple regression analysis. The results support all the four hypotheses. The findings tend to support that lean practices should be implemented collectively and comprehensively, rather than piecemeal and in limited subsets, and that lean practices have positive and significant impact on operations performance.